Cardiometabolic implications of triglyceride–glucose index, remnant cholesterol, and vitamin D in normoglycemic Arab adolescents: a cross-sectional study - Amer, Osama E.; Sabico, Shaun; Alnaami, Abdullah M.; Wani, Kaiser; Al-Daghri, Nasser M. (Frontiers in Endocrinology, 2026)
IntroductionThe triglyceride-glucose (TyG) index, remnant cholesterol (RC), and vitamin D deficiency (VDD) are linked to cardiovascular diseases (CVDs) in adults. Nonetheless, their interplay in adolescents remains unclear. This observational study investigated associations of TyG index, RC, and vitamin D (VD) status with cardiometabolic risk factors in normoglycemic adolescents.MethodsIn this cross-sectional, school-based study, 4,865 apparently healthy adolescents (12–17 years; 64.2% girls) were recruited from 60 randomly selected preparatory and secondary schools across Riyadh, Saudi Arabia (data collection: Sep–Nov 2023). Anthropometrics, blood pressure (BP), fasting glucose (FG) and lipid profile, and serum 25(OH)D were measured using standardized procedures. TyG and RC were calculated and analyzed as both continuous variables and by tertiles. Associations with cardiometabolic outcomes were assessed using multivariable linear and logistic regression adjusted for age and BMI; p-values were corrected for multiple testing using the False Discovery Rate (FDR) (Benjamini–Hochberg). Logistic models include Hosmer–Lemeshow and AUC metrics to assess calibration and discrimination.ResultsAfter adjustment and FDR correction, higher TyG was robustly associated with adverse lipid profiles (lower HDL-C: β = -0.11, FDR-p < 0.001; higher RC: β = 0.40, FDR-p < 0.001) and with higher TC and LDL-C (FDR-p < 0.001). In tertile analyses, the highest TyG tertile was strongly associated with low HDL-C overall (OR T3 vs T1 = 1.8; FDR-p < 0.001) and was associated with vitamin D deficiency (VDD) and hypertension in boys (VDD in boys: OR = 1.6, 95% CI 1.2–2.2, FDR-p = 0.013; hypertension in boys: OR = 1.5, 95% CI 1.1–2.1, FDR-p = 0.010). Elevated RC (highest tertile) was independently associated with low HDL-C overall (OR T3 vs T1 = 0.7; FDR-p = 0.006) and with VDD in boys (OR = 1.5, 95% CI 1.1–2.0, FDR-p = 0.033). Logistic models showed acceptable calibration (Hosmer–Lemeshow p > 0.05) and modest discrimination (AUCs0.55-0.61, p < 0.001). Sex-stratified analyses revealed stronger TyG–25(OH)D inverse associations in boys than girls.ConclusionTyG and RC are associated with VDD and cardiometabolic risks in normoglycemic adolescents, particularly in boys. Sexual dimorphisms were evident, with boys showing higher TyG index and VD levels, while girls had higher RC values. The TyG index was associated with hypertension and VDD in boys while linked to obesity and low HDL–C in girls. VD is inversely correlated with these risks, which warranting confirmation via randomized trials.